Analisis Faktor-Faktor Yang Memengaruhi Intensi Investor Untuk Berinvestasi Kembali Pada Platform Securities Crowdfunding Syariah - Ichsan Gunawan; Rininta Nurrachmi (Department Islamic Economics, 2024)
This study aims to analyze the factors that influence investors' intentions to repeat invest in the Sharia Securities Crowdfunding Platforms. This study adopted structural equation modelling using the partial least squares approach to test the hypotheses. Based on purposive sampling, the questionnaire was distributed through an survey and received 54 responses. The result demonstrates that investor trust, perceived financial risk and financial return have a strong influence on the intention to reinvest in the Sharia SCF platforms. Furthermore, it was found that service quality and sharia compliance have a significant influence on investor trust.